If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + 3 = -6y + 6 Reorder the terms: 3 + -5y = -6y + 6 Reorder the terms: 3 + -5y = 6 + -6y Solving 3 + -5y = 6 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 3 + -5y + 6y = 6 + -6y + 6y Combine like terms: -5y + 6y = 1y 3 + 1y = 6 + -6y + 6y Combine like terms: -6y + 6y = 0 3 + 1y = 6 + 0 3 + 1y = 6 Add '-3' to each side of the equation. 3 + -3 + 1y = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 1y = 6 + -3 1y = 6 + -3 Combine like terms: 6 + -3 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 0=128t+-16t^2 | | h=128t-16t^2 | | 2x^2+24x-14=0 | | 33-4x=5x+21 | | 8+2y=10 | | y=8+3 | | 2y-3x=27y-18x | | 7m+3n+n+5+m-3n+8= | | 16+2x=94-x | | 10y^2+17y+6=0 | | 4+x^3=26+x | | 4+x^3=26 | | x^3=201 | | 8x+9=64 | | 5x-9x+20=-2x+6 | | 2d^2+5d-3=0 | | -21w=-2 | | -2(2x+1)=2(-3x+1) | | -2x^2-x=0 | | 4ln(6x)=16 | | x(2x+5)+(2x+5-12)=108 | | 0.875=x/18 | | 157-2x=25x+19 | | 3(2x+1)=x-5 | | y/25=0.96 | | 11-8x=91-22x | | y/24=0.96 | | 8p^3+4p^2= | | m+12=n | | 0.866x=12 | | 0.5x=18 | | (49y^2)+(14yz)+(z^2)= |